MIG-10 Functions with ABI-1 to Mediate the UNC-6 and SLT-1 Axon Guidance Signaling Pathways - (:unkn) unknown (My University, 2012)
Extracellular guidance cues steer axons towards their targets by eliciting morphological changes in the growth cone. A key part of this process is the asymmetric recruitment of the cytoplasmic scaffolding protein MIG-10 (lamellipodin). MIG-10 is thought to asymmetrically promote outgrowth by inducing actin polymerization. However, the mechanism that links MIG- 10 to actin polymerization is not known. We have identified the actin regulatory protein ABI-1 as a partner for MIG-10 that can mediate its outgrowth-promoting activity. The SH3 domain of ABI-1 binds to MIG-10, and loss of function of either of these proteins causes similar axon guidance defects. Like MIG-10, ABI-1 functions in both the attractive UNC-6 (netrin) pathway and the repulsive SLT-1 (slit) pathway. Dosage sensitive genetic interactions indicate that MIG-10 functions with ABI-1 and WVE-1 to mediate axon guidance. Epistasis analysis reveals that ABI-1 and WVE-1 function downstream of MIG-10 to mediate its outgrowth-promoting activity. Moreover, experiments with cultured mammalian cells suggest that the interaction between MIG-10 and ABI-1 mediates a conserved mechanism that promotes formation of lamellipodia. Together, these observations suggest that MIG-10 interacts with ABI-1 and WVE-1 to mediate the UNC-6 and SLT-1 guidance pathways.
Keywords: Axons; MIG-10